IRANIAN EFL STUDENTS’ ENGAGEMENT, MOTIVATION, AND ATTITUDE TOWARDS TEACHERS’ USE OF HUMOR - Hamze Reese, Zahra; Mousapour Negari, Giti (LLT Journal: A Journal on Language and Language Teaching, 2025)
Although humor in language teaching has received limited scholarly attention, research has consistently highlighted its considerable benefits. It is widely believed that incorporating humor can foster positive attitudes toward learning English. This study aimed to explore the relationship between EFL students’ engagement and motivation, and their perceptions of teachers’ use of humor in language teaching. It also sought to examine the relationship between students’ engagement in the classroom and their motivation to learn. The participants comprised 120 Iranian EFL students from various high schools in Kerman Province. To collect the required data, three questionnaires of course engagement, learning motivation, and students’ attitudes toward teachers’ use of humor were administered. Results of the Pearson product-moment correlation analyses revealed a significant association between course engagement and attitudes toward teachers’ use of humor in the classroom. Moreover, a statistically significant correlation was observed between EFL students’ motivation and attitudes toward teacher humor. Finally, a significant relationship was found between students’ course engagement and their learning motivation. These findings suggest that humor can enhance EFL students’ engagement and motivation, although its impact may vary depending on contextual and individual factors.